Succession of microbial population during natural fermentation of virgin coconut oil - Patino, Barbara C. (2006., 2007)
This study aimed to determine the microbial succession of VCO during fermentation. The no-heat VCo was fermented in a laboratory scale using the process employed by a registered manufacturer. Druring fermentation, changes in pH, titrable acidity (as % lactic acid), free fatty acid (as % lauric acid) and % oil yield were monitored. The microbial quality of raw materials was analyzed prior to the determination of microbial succession during fermentation. The microbial analyses done were total plate (TP), lactic acid bacteria (LAB), yeast and mold (YM), lipolytic microorganism (LM), proteolytic microorganism (PM) and acetic acid bacteria (AAB) counts. Briefly, the process for VCO production involved raw material selection, coconut-splitting, milk extraction, fermentation, oil separation, aging, filling and sealing. During fermentation, the pH of coconut milk decreased as titrable acidity increased. A considerable oil yield of 9.99% was obtained only after the 6th h which gradually increased until a maximum oil yield of 15.89% was obtained on the 16th h. The % oil yield, however, decreased thereafter, On the other hand, no specific trend in FFA values was observed during fermentation. The liquid endosperm obtained the lowest counts in all microbiological tests conducted. On the other hand, the thick coconut milk obtained the highest LAB, YM, PM and AAB counts, whereas, the thin coconut milk obtained the highest TP and LM counts. During fermentation, TPC gradually increased until a maximum of 12.& log cfu ml^-1 was obtained on the 16th h, and i gradually tapered thereafter. A similar increasing trend was observed with LAB until the 10th h with 11.39 log cfu ml^-1 after which a decreasing trend was observed. However, YMC showed peaks during the 5th and 14th h. The LM grew only until the 8th h. The AAB count was highest during the 8th h after which it gradually declined. Results of this study may be used to standardize the process for the no-heat fermented VCO. It is recommended that the specific microorganisms involved in VCO fermentation be identified, the biochemical changes during fermentation be further studied to fully understand the process.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Virgin coconut oil